Neurorestoration Improves Functional Recovery After Stroke - Mosley, Mary (MD Conference Express, 2015)
After an acute stroke, neurologic deficit can be limited and functional recovery can be improved with neurorestorative therapies, including stem cells and exosomes that enhance the spontaneous remodeling that occurs in the brain, spinal cord, and throughout the body. Neurorestoration complements traditional approaches to treating the brain lesion, such as with a tissue plasminogen activator and endovascular therapy.